Blood biomarkers for cognitive decline and clinical progression in a Mexican American cohort. Issue 1 (24th March 2022) - Gonzales, Mitzi M.; Wang, Chen‐Pin; Short, Meghan I.; Parent, Danielle M.; Kautz, Tiffany; MacCarthy, Daniel; Satizabal, Claudia L.; González, David Andrés; Royall, Donald R.; Zare, Habil; O'Bryant, Sid; Maestre, Gladys E.; et al.
Abstract: Introduction : The clinical translation of biofluid markers for dementia requires validation in diverse cohorts. The study goal was to evaluate if blood biomarkers reflecting diverse pathophysiological processes predict disease progression in Mexican American adults. Methods : Mexican American adults (n = 745), 50 years of age and older, completed annual assessments over a mean of 4 years. Serum collected at baseline was assayed for total tau, neurofilament light (NFL), ubiquitin carboxyl‐terminal hydrolase LI, glial fibrillary acidic protein (GFAP), soluble cluster of differentiation 14 (sCD14), and chitinase‐3‐like protein 1 (YKL‐40). Results : Higher GFAP and NFL were associated with global cognitive decline. Only GFAP was associated with increased incident dementia risk (hazard ratio: 1.611 (95% confidence interval: 1.204‐2.155)) and inclusion of additional biomarkers did not improve model fit. Discussion : Among a panel of six blood biomarkers previously associated with neurodegenerative disease, only GFAP predicted incident dementia in our cohort. The findings suggest that blood GFAP levels may aid dementia‐risk prediction among Mexican American adults.